2010
DOI: 10.1542/peds.2009-0925
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Postconcussion Syndrome in Pediatric Mild Traumatic Brain Injury

Abstract: Among school-aged children with mTBI, 13.7% were symptomatic 3 months after injury. This finding could not be explained by trauma, family dysfunction, or maternal psychological adjustment. The results of this study provide clear support for the validity of the diagnosis of PCS in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
447
3
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 549 publications
(470 citation statements)
references
References 30 publications
13
447
3
3
Order By: Relevance
“…34 Among children treated in an emergency room after mTBI, those aged >6 years reported higher rates of persistent symptoms 3 months post injury than did those aged <6 years. 35 Of course, the ability to acquire accurate information about concussion symptoms in children <6 years of age may be limited by a lack of selfawareness of symptoms and the necessary verbal skills to effectively communicate those symptoms. Also, direct comparison of injury severity is not possible from these reports; in fact, the physical heterogeneity of various injuries, taken together with the individual's innate capacity to recover from concussion, makes such comparisons highly challenging.…”
Section: Recoverymentioning
confidence: 99%
“…34 Among children treated in an emergency room after mTBI, those aged >6 years reported higher rates of persistent symptoms 3 months post injury than did those aged <6 years. 35 Of course, the ability to acquire accurate information about concussion symptoms in children <6 years of age may be limited by a lack of selfawareness of symptoms and the necessary verbal skills to effectively communicate those symptoms. Also, direct comparison of injury severity is not possible from these reports; in fact, the physical heterogeneity of various injuries, taken together with the individual's innate capacity to recover from concussion, makes such comparisons highly challenging.…”
Section: Recoverymentioning
confidence: 99%
“…13,16,[41][42][43][44][45][46][47] To study similarities and differences between pediatric and adult SRC, we evaluated a small cohort of children with SRC and healthy controls, using ImPACT neurocognitive testing and MRI measures of brain structure, metabolism, organization, and blood flow. Based on the findings of previous investigations, we hypothesized that (1) structural changes would be minimal by conventional MRI with DTI and SWI;…”
Section: Discussionmentioning
confidence: 99%
“…Les patients qui prenaient à la fois de l'ibuprofène et de l'acétaminophène (79,0 %) ou de l'ibuprofène seul (61,0 %) étaient plus susceptibles d'avoir repris l'école une semaine après leur commotion que ceux qui prenaient de l'acétaminophène (33,3 %) et le groupe témoin (21,1 %). Postinjury concussions and headaches are increasingly recognized as significant problems for children and youth who sustain mild traumatic brain injuries (mTBIs) (1)(2)(3)(4)(5)(6)(7). Headache is the most commonly reported symptom of concussion (2-4) and a symptom of postconcussive syndrome (PCS) (5).…”
unclassified
“…Postinjury concussions and headaches are increasingly recognized as significant problems for children and youth who sustain mild traumatic brain injuries (mTBIs) (1)(2)(3)(4)(5)(6)(7). Headache is the most commonly reported symptom of concussion (2-4) and a symptom of postconcussive syndrome (PCS) (5). Researchers have reported that post-traumatic headache is more common after mTBI than after a severe traumatic brain injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation